2010
DOI: 10.1007/s10603-010-9124-7
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Harried Leisure Class in Contemporary Society: Time-Use Surveys and Patterns of Leisure Time Consumption

Abstract: Time-use patterns, Leisure time consumption, Optimal matching, Harried leisure class, Work-leisure paradoxes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
5
25
1
1
Order By: Relevance
“…Our research is most similar to the work of researchers using sequence analysis (Glorieux et al 2008, 2010; Hellgren 2014; Lesnard 2004, 2008; Lesnard and de Saint Pol 2009; Lesnard and Kan 2011; Minnen et al 2015). Like these scholars, we use the detailed activity data available from time diaries to analyze sequences of activities.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our research is most similar to the work of researchers using sequence analysis (Glorieux et al 2008, 2010; Hellgren 2014; Lesnard 2004, 2008; Lesnard and de Saint Pol 2009; Lesnard and Kan 2011; Minnen et al 2015). Like these scholars, we use the detailed activity data available from time diaries to analyze sequences of activities.…”
Section: Introductionsupporting
confidence: 77%
“…Though women have more leisure episodes than men, the leisure episode of the longest duration for women is shorter, on average, than men’s longest leisure episode; women’s leisure episodes are also more likely to be accompanied by unpaid work (Bittman and Wajcman 2000). The timing and sequence approach considers the overlap/non-overlap between work schedules (Lesnard 2004, 2008), typical work patterns (Glorieux et al 2008; Hellgren 2014; Lesnard and de Saint Pol 2009; Lesnard and Kan 2011; Minnen et al 2015), and leisure patterns (Glorieux et al 2010) to understand what and for whom different sequencing patterns exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work has shown that various types of consumption (e.g., eating, television watching) tend to occur at certain times of the day for most people. However, this work has also shown that different temporal patterns of consumption hold for different groups of people (34).…”
Section: Temporal Patterning Of Everyday Lifementioning
confidence: 69%
“…Indeed, following the large-scale Multinational Time Budget Research Project that was conducted in the 1960s (Szalai et al 1972), a considerable number of countries began funding national time use surveys on a regular basis, resulting in a broad pool of data from developed as well as developing countries. Time diary data are increasingly used for a wide range of analytic purposes, such as documenting the shifting balance between paid and unpaid work (Gershuny 2000), changing lifestyles and consumer behavior (Glorieux et al 2010), parental childcare practices and children’s daily life (Bianchi and Robinson 1997; Hofferth and Sandberg 2001), and urban planning (Harvey 2002). Policies promoting gender equality, environmental protection, and quality of life have greatly benefited from time diary evidence, prompting international agencies such as the United Nations and the International Labour Organization to recommend the regular collection of time use surveys (United Nations Economic Commission for Europe 2013).…”
Section: Introductionmentioning
confidence: 99%